Potensi Delima (Punica Granatum) dalam Kajian Qur'an dan Sunnah - Resmisari, Ruri Siti; Syarifah, Umaiyatus; Holil, Kholifah; Hanifah, Lil (Es-Syajar:Journal of Islam, Science and Technology Integration, 2024)
Pomegranate (Punica granatum) occupies a special place in Islamic tradition and modern health literature. This article aims to explore the potential of pomegranate from the perspective of the Qur'an and Sunnah, as well as to examine the health benefits substantiated by scientific research. Pomegranate is mentioned in several verses of the Qur'an, such as in Surah al-An'am (6): 99 and Surah Ar-Rahman (55): 68, highlighting its significance as a symbol of Allah's power. Hadith also recommend the consumption of pomegranate, indicating its spiritual and medicinal properties.Previous research has demonstrated that pomegranate possesses antioxidant and anti-inflammatory properties, and it has the ability to reduce the risk of heart disease and cancer. Studies confirm that pomegranate consumption can mitigate oxidative stress, inflammation, and cancer cell proliferation. This article compiles and analyzes data from various literature sources using a systematic literature review method.The findings of this review indicate that pomegranate has significant religious and health benefits, rendering it an important fruit in a healthy diet and alternative medicine. Further research is necessary to explore the applications of pomegranate in modern health therapies more comprehensively.